La letteratura cristiana nell'Islanda medievale - DEL ZOTTO, Carla (Carocci, 2010)
This article attempts to investigate the relevance of Latin scholarship and Christianization to Icelandic literature. Iceland’s outstanding production of sagas and poems in the Middle Ages may well be considered as the result of a literacy brought to the island by the first missionary bishops and later enhanced by the religious houses. Hagiographical features and a clerical approach are in fact apparent in historical and narrative works of Icelandic vernacular literature.